Azithromycin-carrying and microtubule-orientated biomimetic poly (lactic-co-glycolic acid) scaffolds for eyelid reconstruction - Xu, Peifang; Chen, Pengjie; Gao, Qi; Sun, Yiming; Cao, Jing; Wu, Han; Ye, Juan (Frontiers in Medicine, 2023)
Introduction Tarsal plate repair is the major challenge of eyelid reconstruction for the oculoplastic surgeon. The ideal synthetic tarsal plate substitute should imitate the microstructure and mechanical strength of the natural eyelid. The aim of this work was to develop a novel bionic substitute for eyelid reconstruction. Methods Three types of poly(lactic-co-glycolic acid) (PLGA) scaffolds (random, oriented, and azithromycin-loaded oriented scaffolds) were prepared using an improved thermal-induced phase separation technique. The microstructure of the scaffolds was examined by scanning electron microscopy. In vitro cytotoxicity was assessed using scaffold extracts. Fibroblast and primary rat meibomian gland epithelial cells (rMGCs) were cultured within the scaffolds, and their behavior was observed using fluorescence staining. Three types of PLGA scaffolds were implanted into rabbit eyelid defect in vivo to evaluate their inductive tissue repair function. Results We successfully fabricated three types of PLGA scaffolds with varying pore architectures, and the axially aligned scaffold demonstrated interconnected and vertically parallel channels. In vitro cytotoxicity tests using scaffold extracts revealed no apparent cytotoxicity. Fluorescence staining showed that both Fibroblast and rMGCs could adhere well onto the pore walls, with fibroblast elongating along the axially aligned porous structure. At 8 weeks post-implantation, all scaffolds were well integrated by fibrovascular tissue. The axially aligned scaffold groups exhibited faster degradation compared to the random scaffold group, with smaller fragments surrounded by mature collagen fibers. Conclusion The study found that the axially aligned scaffolds could well support and guide cellular activities in vitro and in vivo. Moreover, the axially aligned scaffold group showed a faster degradation rate with a matched integration rate compared to the random scaffold group. The findings suggest that the oriented scaffold is a promising alternative for eyelid tarsal plate substitutes.